Long-acting dolutegravir formulations prevent neurodevelopmental impairments in a mouse model - Foster, Emma G.; Sillman, Brady; Liu, Yutong; Summerlin, Micah; Kumar, Vikas; Sajja, Balasrinivasa R.; Cassidy, Adam R.; Edagwa, Benson; Gendelman, Howard E.; Bade, Aditya N. (Frontiers in Pharmacology, 2023)
The World Health Organization has recommended dolutegravir (DTG) as a preferred first-line treatment for treatment naive and experienced people living with human immunodeficiency virus type one (PLWHIV). Based on these recommendations 15 million PLWHIV worldwide are expected to be treated with DTG regimens on or before 2025. This includes pregnant women. Current widespread use of DTG is linked to the drug’s high potency, barrier to resistance, and cost-effectiveness. Despite such benefits, potential risks of DTG-linked fetal neurodevelopmental toxicity remain a concern. To this end, novel formulation strategies are urgently needed in order to maximize DTG’s therapeutic potentials while limiting adverse events. In regard to potential maternal fetal toxicities, we hypothesized that injectable long-acting nanoformulated DTG (NDTG) could provide improved safety by reducing drug fetal exposures compared to orally administered native drug. To test this notion, we treated pregnant C3H/HeJ mice with daily oral native DTG at a human equivalent dosage (5 mg/kg; n = 6) or vehicle (control; n = 8). These were compared against pregnant mice injected with intramuscular (IM) NDTG formulations given at 45 (n = 3) or 25 (n = 4) mg/kg at one or two doses, respectively. Treatment began at gestation day (GD) 0.5. Magnetic resonance imaging scanning of live dams at GD 17.5 was performed to obtain T1 maps of the embryo brain to assess T1 relaxation times of drug-induced oxidative stress. Significantly lower T1 values were noted in daily oral native DTG-treated mice, whereas comparative T1 values were noted between control and NDTG-treated mice. This data reflected prevention of DTG-induced oxidative stress when delivered as NDTG. Proteomic profiling of embryo brain tissues harvested at GD 17.5 demonstrated reductions in oxidative stress, mitochondrial impairments, and amelioration of impaired neurogenesis and synaptogenesis in NDTG-treated mice. Pharmacokinetic (PK) tests determined that both daily oral native DTG and parenteral NDTG achieved clinically equivalent therapeutic plasma DTG levels in dams (4000-6500 ng/mL). Importantly, NDTG led to five-fold lower DTG concentrations in embryo brain tissues compared to daily oral administration. Altogether, our preliminary work suggests that long-acting drug delivery can limit DTG-linked neurodevelopmental deficits.